Electricity production from black liquor: a novel integrated system. (December 2017) - Darmawan, Arif; Hardi, Flabianus; Yoshikawa, Kunio; Aziz, Muhammad; Tokimatsu, Koji
Abstract: Energy recovery from black liquor (BL) can be performed through gasification process at temperatures above the melting point of the inorganic chemicals. Complementing the BL gasification experimental research, this study is conducted to simulate the thermodynamic modeling of integrated system for BL evaporation, gasification and combined cycle for power generation. BL evaporation system is initially proposed based on the concept of exergy recovery which can minimize the exergy loss, hence lower the required energy input for evaporation. In the proposed BL evaporation system, higher target solids content leads to lower total required energy for BL evaporation. The lowest required total energy for evaporation can be achieved at target solids content of 75 wt% wb. Furthermore, an integrated power generation adopting gasification and combined cycle is modeled and application of different BL evaporation technologies is also evaluated in terms of net energy efficiency. The integrated system with exergy recovery-based evaporation can achieve the net energy efficiency of 34.5%, which is significantly higher than adoption of multi-effect evaporators (24.5%) and conventional boiler-based evaporation (14.7%).